Representasi Gentle Parenting dalam Konten YouTube: Studi Semiotika Kanal Nikita Willy Official - Gucci, Mayang Sari; Rachmawati, Farikha (KOMUNIKA, 2025)
The development of digital technology has brought major changes to communication patterns and social behavior, including in the realm of parenting. Social media platforms, notably YouTube, have become primary sources of parenting guidance for young parents in Indonesia, replacing traditional resources such as books and direct consultations. This study aims to describe the representation of gentle parenting, as conceptualized by Sarah Ockwell-Smith, in Nikita Willy’s YouTube content, using John Fiske’s semiotic analysis framework. A qualitative research method with a descriptive analytical approach was employed, with data collected through documentation of three most-viewed videos related to gentle parenting on the “Nikita Willy Official” YouTube channel. The analysis identified Fiske’s three levels of representation: reality, representation, and ideology. Findings indicate that gentle parenting is portrayed through gentle interactions, positive communication, and an emphasis on understanding children’s emotions, avoiding physical punishment and psychological pressure. Nikita Willy’s content exemplifies empathetic, respectful, and understanding parenting practices, with clear yet supportive boundaries, aligning with Sarah Ockwell-Smith’s gentle parenting principles. These findings are supported by a literature review of journal and non-journal sources, highlighting the role of digital media in shaping modern parenting interpretations. The study concludes that Nikita Willy’s representation of gentle parenting serves as a positive reference for young parents, promoting the adoption of humanistic parenting approaches in Indonesian society, which is predominantly characterized by authoritative parenting styles.